The immunostimulatory effects of fucoidan on the cellular and humoral immune response in Wistar rats - Rochmah Kurnijasanti; Giftania Wardani; Muhammad Rais Mustafa; Sri Agus Sudjarwo (Open Veterinary Journal)
Background: Natural product active ingredients are currently being studied rigorously worldwide and offer a viable substitute for traditional immunotherapy for various medical disorders. Aim: The objective of the study was to investigate the immunostimulatory properties of fucoidan in albino Wistar rats. Methods: For the current study, forty rats were divided into five groups of rats that were used in good condition. In-vivo experiments of fucoidan were carried out in Wistar albino rats, such as the cyclophosphamide-caused myelosuppression, the delayed-type hypersensitivity (DTH) response, the phagocytic activity, the haemagglutinating antibody (HA) titer, and the neutrophil adhesion test. Results: The phagocytic index increased significantly in response to Fucoidan in a dose-dependent manner, as well as enhanced DTH reaction, and HA titer caused by sheep red blood cells sheep red blood cells. Additionally, fucoidan decreased myelosuppression in rats after cyclophosphamide treatment and enhanced neutrophil adhesion with nylon f iber. Conclusion: These findings imply that fucoidan has immunostimulant properties and could potentially utilised to treat immune-depression diseases. [Open Vet J 2024; 14(8.000): 1794-1800]